Yeasts in natural ecosystems : diversity - Buzzini, Pietro; Lachance, Marc-André; Yurkov, Andrey (Springer, 2017)
This book focuses on the diversity of yeasts in aquatic and terrestrial ecosystems, including the association of yeasts with insects, invertebrate and vertebrate animals. It offers an overview of the knowledge accumulated in the course of more than 60 years of research and is closely connected with the volume Yeasts in Natural Ecosystems: Ecology by the same editors. In view of the rapid decline of many natural habitats due to anthropogenic activities and climate change, the need to study biodiversity is pressing. Rising temperatures threaten species inhabiting cold and aquatic environments, and species in terrestrial ecosystems are endangered by habitat fragmentation or loss. Most of our knowledge of intrinsic properties (autoecology) of yeasts reported throughout this book is derived from laboratory experiments with pure cultures. Accordingly, the importance of culture collections for ecological studies is highlighted by presenting an overview of worldwide available yeast strains and their origins. All of the chapters were written by leading international yeast research experts, and will appeal to researchers and advanced students in the field of microbial diversity.
Keywords: Yeast.; Microbial ecology.; Yeast fungi -- Biotechnology.; elektronické knihy; electronic books